(untitled) (Shiksha Shastra Saurabh, 2024)
Sustainable development is a movement toward improving the world, not just a passing trend . In Nepal, universities and Higher Education Institutions (HEIs) have yet to effectively fulfill their responsibility to promote sustainability . This study explores the sustainability perception of higher education (HE) by community-based HEIs, i.e., community colleges . A literature review indicates the benefits and threats of sustainability consciousness which is supplemented by primary and secondary data collected through interviews with high-ranking UGC and university officials and former Chairpersons of the Nepal Public Campus Association (NPCA) . The thematic analysis reveals that community colleges of Nepal are facing their identity crisis and struggling for their own sustainability with implications to fulfill the SDGs . Lack of uniform regulations, absence of sustainability-friendly curricula, declining student enrollment, ineffective management, conventional pedagogy, inadequate and poor research activities, unstable human resources, insufficient financial support, and inadequate eco-friendly infrastructure stand as key challenges . However, prospects are there that quality accredited community colleges can foster sustained growth by ensuring accessible, high-quality education along with strong leadership, governance, and community involvement . Their expected role in mitigating global warming, promoting gender equity, reducing carbon emissions, and bridging educational gaps makes them highly visible to achieving SDGs . This study recommends some strategic measures for addressing sustainability challenges, paving the way for making Nepal a more prosperous and sustainable country in the days to come.